Étude de la professionnalisation des masseurs-kinésithérapeutes salariés à partir de leurs usages des courriers électroniques - Anne Pilotti (Éducation et Socialisation)
A movement of professionalization started 20 years ago, affects the French paramedical professions. Professional writing, which is an issue for these different professions, takes many forms. Institutional electronic messaging, created by healthcare institutions, is a form of professional writing but also a management tool. The contribution concerns the professionalization of salaried physiotherapists, approached from their uses of institutional electronic mail. The ethnographic approach, implemented in three health establishments, includes participant observations, interviews and writings. The theoretical framework of institutional analysis makes it possible to work on professionalization as an institutionalization of professional practices and standards . The results show the positioning of these professionals, the place given to professional networks, to the various institutional territories and to the patient’s body.